2021
DOI: 10.1039/d1mh00018g
|View full text |Cite
|
Sign up to set email alerts
|

Flexible temperature sensors made of aligned electrospun carbon nanofiber films with outstanding sensitivity and selectivity towards temperature

Abstract: Continuous real-time measurement of body temperature using a wearable sensor is an essential part of human health monitoring. Electrospun aligned carbon nanofiber (ACNF) films are employed to assemble flexible temperature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Even any material with a carbon backbone can be used as a precursor for carbon materials, PAN is the most commonly used carbon precursor due to its high carbon yield up to 56%, flexibility for maintaining the structure, excellent mechanical and electrochemical properties [48,49]. PAN based carbon nanofibers have been used in many fields including electrodes [5056], supercapacitors [5763], fuel cells [6467], sensors [6872], solar cells [7375], biomedical applications [76] and tissue engineering applications [7781]. For instance, Kumar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Even any material with a carbon backbone can be used as a precursor for carbon materials, PAN is the most commonly used carbon precursor due to its high carbon yield up to 56%, flexibility for maintaining the structure, excellent mechanical and electrochemical properties [48,49]. PAN based carbon nanofibers have been used in many fields including electrodes [5056], supercapacitors [5763], fuel cells [6467], sensors [6872], solar cells [7375], biomedical applications [76] and tissue engineering applications [7781]. For instance, Kumar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional temperature measurement equipment, including mercury thermometer and infrared thermometer, can only achieve measurement at a given point of time. They cannot provide real-time temperature data [12]. In order to reach continuous and stable temperature monitoring, comfortable flexible temperature sensors are needed and will be widely applied in the temperature monitoring of wearable products [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…reported highly flexible and sensitive temperature sensors based on aligned carbon nanofiber (ACNF) films (Figure 11f). [ 187 ] According to the experimental results, the sensor exhibited a remarkable temperature sensitivity at 1.52% °C −1 , known as the most sensitive sensor in the existing carbon‐based sensors. Meanwhile, it was found that the carbonization temperature was significant in sensitivity control by adjusting atomic structures of ACNFs.…”
Section: Structures‐derived Propertiesmentioning
confidence: 99%
“…f) ΔR/R 0 of the sensor against temperature ranging from 30 to 55 °C for 300 cycles showing excellent durability. Reproduced with permission [187]. Copyright 2021, Royal Society of Chemistry.…”
mentioning
confidence: 99%